The favorites : [large type] a novel - Hennigan, Rosemary (Center Point Large Print, 2024)
"Most students would kill to be accepted into the prestigious Law and Literature cohort at Franklin University. But for Jessie Mooney, enrollment in the course is about more than elite campus status, rigorous thought, and professional connections. It's her chance to get close to charismatic professor Jay Crane -- and take him down. From the moment she discovered their secret relationship, Jessie's been convinced Crane is to blame for the events leading to her sister's death. Still haunted by their last email exchange -- You know what you did -- she'll cross any line to hold him accountable. But when Jessie finally earns Crane's trust and the coveted position as one of his "favorites," attracting the other students' envy and suspicion, the truth becomes darkly twisted. Is it justice Jessie craves, or revenge? And what does she stand to lose if she gets her way?"--